2002
DOI: 10.1046/j.1439-0280.2002.02048.x
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of three weed species to polyphagous predators 
and their influence on aphid populations in adjacent lettuce cultivations

Abstract: The utilization of olfactory responses of predators and parasitoids to the allelochemicals emitted by phytophagous arthropods and their host plants is becoming more important in biological pest control. The effects of three weed species, i. e. wormwood Artemisia vulgaris L., tansy Tanacetum vulgare L. and stinging nettle Urtica dioica L., which were planted as accompanying vegetations into a lettuce field, were examined for the predatory species Coccinella septempunctata L., Adalia bipunctata (L.), Propylea qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
12
0
4
Order By: Relevance
“…These patches supported only low densities of pea aphids, apparently because of the local build -up in ladybird numbers. Similarly, Sengonca et al (2002) found that C. septempunctata , A. bipunctata and P. quatuordecimpunctata the landscape matrix in which individual fi elds of alfalfa occur (e.g. percentage of the surrounding landscape that is wetlands, woodlands or crops) can sometimes overshadow the direct numerical response of ladybirds ( Hip.…”
Section: Factors O Ther T Han F Ocal P Rey D Ensitymentioning
confidence: 95%
“…These patches supported only low densities of pea aphids, apparently because of the local build -up in ladybird numbers. Similarly, Sengonca et al (2002) found that C. septempunctata , A. bipunctata and P. quatuordecimpunctata the landscape matrix in which individual fi elds of alfalfa occur (e.g. percentage of the surrounding landscape that is wetlands, woodlands or crops) can sometimes overshadow the direct numerical response of ladybirds ( Hip.…”
Section: Factors O Ther T Han F Ocal P Rey D Ensitymentioning
confidence: 95%
“…Muller and Godfray (1997) demonstrated an earlier population decline in nettle aphid colonies adjacent to grass plots as a result of migration. Accompanying weed strips with olfactorily attractive plants can also contribute to the promotion of predators (e.g., ladybirds) in biological pest control (Sengonca et al , 2002). Ryegrass is a type of forage grass that has some agronomic characters, such as abundant tillers, strong resistibility, and earlier maturation than wheat.…”
Section: Discussionmentioning
confidence: 99%
“… Wanneer natuurlijke vijanden niet kunnen overleven in de akkers en plantages moeten de semi(natuurlijke) habitats rond de akkers dienst doen als refugia. Verschillende studies hebben aangetoond dat de (semi)natuurlijke habitatfragmenten tussen de velden een diversiteit aan natuurlijke vijanden herbergen zoals loopkevers, kortschildkevers, spinnen, lieveheersbeestjes, zweefvliegen, gaasvliegen, roofmijten en -wantsen, allerlei parasitoïden en insectivore vogels (Varchola & Dunn, 2001;Maudsley et al, 2002;Sengonca et al, 2002;. Die (semi)natuurlijke habita ts zijn relatief ongestoord en permanent aanwezig waardoor ze dienst doen als een reservoir voor deze soorten.…”
Section: Natuurlijke Bestuiving (En Bestuiving Door Honingbijen) En Gunclassified